Isolated idiopathic right ventricular dilated cardiomyopathy - Swapan Samanta; Rajesh Vijayverghia; Kim Vaiphei (Wolters Kluwer Medknow Publications, 2011)
Isolated idiopathic right ventricular dilated cardiomyopathy is rare and is a diagnosis by exclusion. There is a distinct male predominance. The usual clinical presentations are syncope, ventricular tachycardia, left bundle branch block on ECG and right heart failure. Diagnosis is usually established based on the clinical and laboratory parameters. Confirmation of the same is done by studying the pathological features of the heart in an endomyocardial biopsy or at post-mortem. Herein we report a case of this rare entity which was diagnosed clinically and was further confirmed at autopsy.